PERTUMBUHAN SEKTOR PARIWISATA DALAM PERSPEKTIF MAQASHID SYARIAH DI KABUPATEN BANYUWANGI - Fajar Isnaeni; Nur Anim Jauhariyah; Mahmudah; Ainur Rizqiyah (Universitas KH. Mukhtar Syafaat, 2026)
Tourism is a strategic sector that contributes significantly to national and regional economic development. This study aims to examine the impact of tourism sector fluctuations on regional macroeconomics, using a case study in Banyuwangi Regency. The research method applied is descriptive qualitative, analyzing secondary data on tourist visitation trends from the pre-pandemic to the post-pandemic periods of COVID-19 and their effects on regional economic growth. The document analysis reveals that Banyuwangi's tourism sector reached its peak performance in 2019, recording 5.307.054 domestic and 101.622 international tourist arrivals. However, the onslaught of the COVID-19 pandemic in 2020–2021 triggered a drastic decline in visitations due to mobility restrictions, which directly resulted in a -3.58% contraction in Banyuwangi Regency's economic growth in 2020. This study concludes that there is a highly close interconnection between the stability of the tourism industry and the economic resilience of the local community, emphasizing the need for adaptive and sustainable tourism recovery strategies to maintain regional economic resilience in the future